Heletz experimental site overview, characterization and data analysis for CO2 injection and geological storage. (May 2016) - Niemi, Auli; Bensabat, Jacob; Shtivelman, Vladimir; Edlmann, Katriona; Gouze, Philippe; Luquot, Linda; Hingerl, Ferdinand; Benson, Sally M.; Pezard, Philippe A.; Rasmusson, Kristina; Liang, Tian; Fagerlund, Fritjof; et al.
Highlights: Saline aquifer characterization. Site characterization for scientifically motivated CO2 injection experiments. Geological and hydrogeological model, characteristics of reservoir and cap-rock. Baseline conditions, petrophysical properties, geostatistics. Abstract: This paper provides an overview of the site characterization work at the Heletz site, in preparation to scientifically motivated CO2 injection experiments. The outcomes are geological and hydrogeological models with associated medium properties and baseline conditions. The work has consisted on first re-analyzing the existing data base from ∼40 wells from the previous oil exploration studies, based on which a 3-dimensional structural model was constructed along with first estimates of the properties. The CO2 injection site is located on the saline edges of the Heletz depleted oil field. Two new deep (>1600 m) wells were drilled within the injection site and from these wells a detailed characterization program was carried out, including coring, core analyses, fluid sampling, geophysical logging, seismic survey, in situ hydraulic testing and measurement of the baseline pressure and temperature. The results are presented and discussed in terms of characteristics of the reservoir and cap-rock, the mineralogy, water composition and other baseline conditions, porosity, permeability, capillary pressure and relative permeability. Special emphasis is given to petrophysical properties of the reservoir and the seal, such as comparing the estimates determined by different methods, looking at their geostatistical distributions as well as changes in them when exposed to CO2 .